Melanin Biopolymers in Pharmacology and Medicine—Skin Pigmentation Disorders, Implications for Drug Action, Adverse Effects and Therapy - Karkoszka, Marta; Rok, Jakub; Wrześniok, Dorota (Pharmaceuticals (Basel, Switzerland), 2024)
Melanins are biopolymeric pigments formed by a multi-step oxidation process of tyrosine in highly specialized cells called melanocytes. Melanin pigments are mainly found in the skin, iris, hair follicles, and inner ear. The photoprotective properties of melanin biopolymers have been linked to their perinuclear localization to protect DNA, but their ability to scavenge metal ions and antioxidant properties has also been noted. Interactions between drugs and melanins are of clinical relevance. The formation of drug–melanin complexes can affect both the efficacy of pharmacotherapy and the occurrence of adverse effects such as phototoxic reactions and discoloration. Because the amount and type of melanin synthesized in the body is subject to multifactorial regulation—determined by both internal factors such as genetic predisposition, inflammation, and hormonal balance and external factors such as contact with allergens or exposure to UV radiation—different effects on the melanogenesis process can be observed. These factors can directly influence skin pigmentation disorders, resulting in hypopigmentation or hyperpigmentation of a genetic or acquired nature. In this review, we will present information on melanocyte biology, melanogenesis, and the multifactorial influence of melanin on pharmacological parameters during pharmacotherapy. In addition, the types of skin color disorders, with special emphasis on the process of their development, symptoms, and methods of treatment, are presented in this article.